Research Trends on Green Accounting, CSR, and Financial Performance in the Context of Firm Value : A Bibliometric Analysis of Indonesian Energy Sector Literature - Amelia Kusniawati; Siti Mujanah; Achmad Yanu Alif Fianto (International Journal of Economics and Management Research, 2025)
This study conducts a bibliometric analysis to explore research trends on Green Accounting, Corporate Social Responsibility (CSR), and financial performance in the context of firm value within Indonesia's energy sector. Utilizing data from 1,000 peer-reviewed articles (2019–2025) sourced from Crossref, the analysis employs Publish or Perish and VOSviewer to map publication trends, thematic clusters, and citation networks. The findings reveal three dominant clusters: (1). Red Cluster (Major): Green Accounting and CSR linked to governance and sustainability, (2). Green Cluster (Major): empirical studies on financial performance and firm value, and (3). Blue Cluster (Minor): emerging themes like green investment and ESG integration. The study highlights inconsistent findings in the literature, such as the mixed impact of Green Accounting on firm value and the mediating role of profitability. By identifying gaps—such as limited sector-specific studies and the need for longitudinal analyses—this research provides a foundation for future inquiries. The practical implications emphasize the strategic alignment of sustainability practices with financial goals, while recommendations call for interdisciplinary approaches and policy-driven frameworks to enhance ESG adoption in Indonesia’s energy sector.